2015
DOI: 10.1038/nature14982
|View full text |Cite
|
Sign up to set email alerts
|

RAF inhibitors that evade paradoxical MAPK pathway activation

Abstract: Oncogenic activation of BRAF fuels cancer growth by constitutively promoting RAS-independent mitogen-activated protein kinase (MAPK) pathway signalling. Accordingly, RAF inhibitors have brought substantially improved personalized treatment of metastatic melanoma. However, these targeted agents have also revealed an unexpected consequence: stimulated growth of certain cancers. Structurally diverse ATP-competitive RAF inhibitors can either inhibit or paradoxically activate the MAPK pathway, depending whether act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
324
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 330 publications
(338 citation statements)
references
References 36 publications
13
324
0
1
Order By: Relevance
“…In cells with BRAF WT they paradoxically activate RAF and ERK signaling, via a RASdependent mechanism that remains incompletely understood. Recently, a number of RAF inhibitors with diverse structural and biochemical properties entered preclinical and clinical development Peng et al, 2015;Zhang et al, 2015). We sought to develop an integrated model of RAF inhibitor action that would explain the biochemical effects of RAF inhibitors based on their structural properties in any cellular context.…”
Section: Introductionmentioning
confidence: 99%
“…In cells with BRAF WT they paradoxically activate RAF and ERK signaling, via a RASdependent mechanism that remains incompletely understood. Recently, a number of RAF inhibitors with diverse structural and biochemical properties entered preclinical and clinical development Peng et al, 2015;Zhang et al, 2015). We sought to develop an integrated model of RAF inhibitor action that would explain the biochemical effects of RAF inhibitors based on their structural properties in any cellular context.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, next-generation RAF inhibitors that evade MAPK pathway reactivation were developed as an alternative strategy to potentiate the suppression of MAPK pathway output in BRAF V600E -driven cancers (28,29). These RAF inhibitors, such as PLX8394, were shown to be effective in BRAF V600E and RASmutant melanoma and colorectal cancer cells (28).…”
Section: G466vmentioning
confidence: 99%
“…These RAF inhibitors, such as PLX8394, were shown to be effective in BRAF V600E and RASmutant melanoma and colorectal cancer cells (28). Unlike melanoma, however, non-V600 BRAF mutant alleles comprise a significant proportion (∌40%) of mutations in LA (30)(31)(32).…”
Section: G466vmentioning
confidence: 99%
“…10) Figure 1b shows representative kinase inhibitors having a number of substituents at various positions in the 7-azaindole ring. [11][12][13][14][15][16] Among them, vemurafenib (1), a B-RAF kinase (serinethreonine kinase [STK]) inhibitor, is the first FDA-approved 7-azaindole-based kinase drug for the treatment of melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…1b. Apart from PLX-8394 (6), a second-generation BRAF kinase inhibitor, 16) other compounds have been developed targeting various kinds of kinases including Janus kinase 3 (JAK3; a cytoplasmic tyrosine kinase [TK]), 12) colony stimulating factor 1 receptor (CSF1R; a receptor TK), 13) aurora kinases (STK), 14) and rho-associated, coiled-coil-containing protein kinase 1 (ROCK1; STK). 15) Comprehensive survey of a drug discovery database (substructure-search using Thomson Reuters Integrity SM database 18) as of March 2017) revealed that more than 90 kinds of kinases have been shown sensitive to 7-azaindole-based kinase inhibitors-sufficient to cover the whole human kinome as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%